EDUCATIONAL DESIGN OF SMALL ARCHITECTURAL FORMS USING THE EXAMPLE OF CREATING A PARK TERRACE WITH A CANOPY - Яновицький, Євген; Галак, Катерина; Селиванов, Олексій; Король, Володимир (SWorldJournal, 2024)
The article examines the issue of identifying the artistic image of the landscape environment, which is achieved by using techniques of architectural composition. The means of landscape composition are highlighted, as the art of placing various elements